Analysis of the MHD partially ionized GO-Ag/water and GO-Ag/kerosene oil hybrid nanofluids flow over a stretching surface with Cattaneo–Christov double diffusion model: A comparative study. (July 2022) - Algehyne, Ebrahem A.; Alharbi, Amal F.; Saeed, Anwar; Dawar, Abdullah; Ramzan, Muhammad; Kumam, Poom
Abstract: This investigation explores the augmentation in thermal characteristics of the hybrid nanoliquid, which has pretty imperative uses in the industries like coolant of various electrical devices, and heat exchangers, etc. keeping in view these important applications, the three-dimensional magnetohydrodynamic flow of partially ionized hybrid nanofluids over a stretching sheet has been considered in this investigation. Two different liquids namely water and kerosene oil is used as base liquids in which the nanoparticles of silver and graphene oxide are mixed to form a hybrid nanofluids. Cattaneo-Christov heat and mass flux model is used in the flow model. An appropriate set of variables is exploited to convert the modeled equations into dimension-free form. The present problem is simulated with the help of homotopic analysis technique. The outcomes of this analysis show that the rising values of Hall current and ion-slip number are enhanced the primary velocities of the kerosene oil-based and water-based hybrid nanofluids, while the greater Hartmann number has declined the primary and secondary velocities of the hybrid nanofluids. On the other hand, the larger values of Hall current and stretching parameter of the sheet have increased the primary and secondary velocities of the hybrid nanofluids, while the opposite impacts are found for increasing ion-slip number and Hartmann number. The temperature profiles of the hybrid nanofluids are weakened for thermal relaxation time parameter, while increased for higher thermal Biot number. It is found that the water-based hybrid nanofluid is greatly influenced by the embedded parameters as compared to the kerosene oil-based hybrid nanofluid.